Genetic variation and heteroplasmy of Varroa destructor inferred from ND4 mtDNA sequences - Muntaabski, Irina; Russo, Romina Maria; Liendo, María Clara; Palacio, María Alejandra; Cladera, Jorge Luis; Lanzavecchia, Silvia Beatriz; Scannapieco, Alejandra Carla (Springer, 2020)
Varroa destructor, a parasitic mite of the western honey bee, Apis mellifera L., is a serious threat to colonies and beekeeping worldwide. Population genetics studies of the mite have provided information on two mitochondrial haplotypes infecting honey bee colonies, named K and J (after Korea and Japan, respectively, where they were originally identified). On the American continent, the K haplotype is much more prevalent, with the J haplotype only detected in some areas of Brazil. The aims of the present study were to assess the genetic diversity of V. destructor populations in the major beekeeping region of Argentina and to evaluate the presence of heteroplasmy at the nucleotide level. Phoretic mites were collected from managed A. mellifera colonies in ten localities, and four mitochondrial DNA (mtDNA) regions (COXI, ND4, ND4L, and ND5) were analyzed. Based on cytochrome oxidase subunit I (COXI) sequencing, exclusively the K haplotype of V. destructor was detected. Furthermore, two sub-haplotypes (KArg-N1 and KArg-N2) were identified from a variation in ND4 sequences and the frequency of these sub-haplotypes was found to significantly correlate with geographical latitude. The occurrence of site heteroplasmy was also evident for this gene. Therefore, ND4 appears to be a sensitive marker for detecting genetic variability in mite populations. Site heteroplasmy emerges as a phenomenon that could be relatively frequent in V. destructor.